Preschoolers Questioning Strategies in Classroom Interactions - Titik Sudartinah (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2021)
Preschoolers often actively participate in conversations by questioning, which come in many forms and serve many functions. This article aims to identify the forms and functions of the questions that preschoolers ask during classroom interactions with their peers and teachers. The research was a qualitative research involving eighteen preschoolers and two teachers. Data were collected by audio-visually recording the questions expressed by the preschoolers during classroom interactions. Their forms and functions were then identified. The findings show that preschoolers mostly use Wh-Questions for both information and non-information seeking, while other forms are mainly for asking for a clarification or confirmation. The employment of these questioning strategies signifies that preschoolers already have the capability of matching the forms of their questions with their functions in order that they can build a complete picture and understanding of the world around them by eliciting, collecting, and synthesizing information from their peers and teachers.